Love as a Hollow: Merleau‐Ponty's Promise of Queer Love. (8th October 2016) - Burke, Megan M.
Abstract : This article argues that Maurice Merleau‐Ponty advances a queer notion of love. In particular, I argue that his notion of love as an institution, as a hollow fueled by the imaginary dimension of existence, shows that love unhinges petrified ideals of gender. I suggest that the crucial insight to be found in Merleau‐Ponty's account of love is that love is a lived openness that invites us to seek out new ways of being.